2017
DOI: 10.1155/2017/2176795
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spherical Nano-SiO2 Content on the Thermal Protection Performance of Thermal Insulation Ablation Resistant Coated Fabrics

Abstract: In the high temperatures experienced in fire, radiant heat accounts for 80% of the total heat flow; therefore, improving the radiation protection is the best way to enhance the thermal protective performance of thermal insulation ablation resistant coated fabrics. To achieve this goal, the coating process and the ingredients used were optimized, spherical nano-SiO 2 and other particles were added, and thermal insulation ablation resistant coated fabrics with high radiant heat reflectivity were prepared. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Additionally, nanoparticles may inhibit polymer disaggregation during curing, resulting in a uniform covering. Nanoparticles having a greater specific surface area are known to improve not only the epoxycuring process but also the nanoparticle dispersion in the epoxy matrix [94], [95]. For polyester coatings, Golgoon et al [96] found that the embedding nano clays created a more uniform and denser coating and fewer pores compared to the pure polyester coating.…”
Section: Authormentioning
confidence: 99%
“…Additionally, nanoparticles may inhibit polymer disaggregation during curing, resulting in a uniform covering. Nanoparticles having a greater specific surface area are known to improve not only the epoxycuring process but also the nanoparticle dispersion in the epoxy matrix [94], [95]. For polyester coatings, Golgoon et al [96] found that the embedding nano clays created a more uniform and denser coating and fewer pores compared to the pure polyester coating.…”
Section: Authormentioning
confidence: 99%
“…To strengthen the reflection radiant heat and heat insulation performance at high temperatures, single-, double- and three-layer coated flexible composites were prepared. Using the three-layer coated flexible composite as an example, its preparation process is shown in Figure 4, which is divided into preparation of the three layers of the heat insulating coating, fireproof heat insulated coating and thermal radiation protective coatings: 18 , 19…”
Section: Preparation Process For the Coated Flexible Compositesmentioning
confidence: 99%
“…To strengthen the reflection radiant heat and heat insulation performance at high temperatures, single-, double-and three-layer coated flexible composites were prepared. Using the three-layer coated flexible composite as an example, its preparation process is shown in Figure 4, which is divided into preparation of the three layers of the heat insulating coating, fireproof heat insulated coating and thermal radiation protective coatings: 18,19 Preparation of the heat insulating coating With the dispersion machine set to 30 min and a speed of 500 r/min, fillers such as aerogel, mica powder, ultrafine kaolin and talcum powder were added slowly into the organic silicone resin in turn, then the coupling agent KH550 was added. 20 After the materials were added, the stirring speed was increased to 1800 r/ min.…”
Section: Preparation Process For the Coated Flexible Compositesmentioning
confidence: 99%
“…Moreover, an increase in the electrical insulating properties of NBR-silica (15-20 phr) nanocomposite based on NBR has been shown the proper electrical insulation properties at 15 phr [4]. It has been investigated that the prepared coated fabrics with 15 wt% of the spherical nano-SiO2 have increased their thermal protection performance due to improving their radiant reflectivity [5]. Physico-mechanical and thermal properties of hydrogenated NBR containing nano-silica have been studied with respect to the characterization of the dispersion and interaction parameters of the rubber with nano fillers were characterized with the help of XRD and SEM [6].…”
Section: Introductionmentioning
confidence: 99%